PERENCANAAN TUBUH BENDUNGANAIR LUAS KABUPATEN KAUR PROVINSI BENGKULU - Firmansyah, Robet; Besperi, Besperi; Fauzi, Muhammad (Universitas Bengkulu, 2017)
The purpose of this study was to plan the dimensions of the dam body that is technically feasible to build, as well as secure the stability. Flood discharge plan used amounted to 1,152 meters cubic/ sec with a return period of 1000 years. Based on the analysis that has been done, get a plan of flood water level is + 303,22 meters, surveillance obtained high of 3,0 meters, the body of the dam crest elevation gained + 306,22 meters high dam that is obtained by subtracting the height elevation of the peak body dam with a base elevation of the dam is 56,16 meters, width of the dam crest beacon of 11.0 meters, rockfill the upstream slope of 1:3 and for rockfill downstream slope is 1: 2,.25. Using the scheme of depression line formation with drainage leg with a graphic way, do not occur out of the body dam seepage and flow filtration capacity value of the calculation, Q = 9,553 x 10-5 meters cubic / sec, smallest than 2% Qinflow mean = 5,785 mmeters cubic / sec, dam secure against flow filtration. The stability of the main dam of landslide with the value of safety factor in a variety of conditions, namely dams both empty and fully charged in a normal state or an earthquake, for rockfill dam by calculating the weight of the dam, sliding moment, pore water pressure and earthquake loads. Using the method of slices Fellenius glide plane, the value obtained above safe rate (1,2), the planneddam safety to landslides